Non-competitive agency and Luther’s experiential argument against virtue - Zahl, Simeon (Wiley, 2018)
This article examines a critique that has been levied against Martin Luther’s account of the passivity of the human agent in salvation, and his corresponding critique of Aristotelian and Scholastic accounts of virtue. According to Reinhard Hütter and Jennifer Herdt, among others, Luther’s theology of passivity is primarily the product of a philosophical failure to recognize that divine and human agency can be conceived in non-competitive terms. In what follows, I will demonstrate through close analysis of Luther’s arguments that this philosophical critique does not succeed in refuting Luther’s theology of passivity. This is because it fails to recognize that Luther’s view of human agency and his critique of virtue are based to a significant degree on a different kind of argument: namely, empirical reflection on the experience of sin, including especially experience of the unmasterability of sinful affections through discipline, habit, or effort of will. I conclude by arguing that until Christian virtue ethicists have reckoned with this experiential argument, they have not engaged with one of the strongest theological critiques of virtue-based paradigms of Christian moral transformation.